2004
DOI: 10.1108/02686900410530501
|View full text |Cite
|
Sign up to set email alerts
|

Management accounting practices in selected Asian countries

Abstract: Traditional management accounting techniques such as standard costing and variance analysis, traditional budgeting and cost volume profit analysis are said to be less useful in the present manufacturing environment. To succeed in the present dynamic business environment, tools or strategies such as JIT, ABC, TQM, process re-engineering, life cycle assessment and target costing would greatly enhance the ability of corporations to meet global competition. Through a literature review, this study examines the exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
124
1
35

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(166 citation statements)
references
References 12 publications
6
124
1
35
Order By: Relevance
“…The adoption rates of contemporary MAPs are disappointing while those of traditional MAPs remain high across different countries including U.K., U.S., Australia, New Zealand, and Asian countries (Adler, Everett & Waldron, 2000;Bright, Davies, Downes & Sweeting, 1992;Chenhall & LangfieldSmith, 1998;Drury, Braund, Osborne & Tayles, 1993;EI-Ebaishi, Karbhari & Naser, 2003;Guilding, Cravens & Tayles, 2000;Phadoongsitthi, 2003;Sulaiman, Ahmad & Alwi, 2004;Szendi & Elmore, 1993). Hence, it may be too early to conclude that traditional MAPs have completely lost their importance, and the adoption of contemporary MAPs may not guarantee the success of organizations.…”
Section: Introductionmentioning
confidence: 99%
“…The adoption rates of contemporary MAPs are disappointing while those of traditional MAPs remain high across different countries including U.K., U.S., Australia, New Zealand, and Asian countries (Adler, Everett & Waldron, 2000;Bright, Davies, Downes & Sweeting, 1992;Chenhall & LangfieldSmith, 1998;Drury, Braund, Osborne & Tayles, 1993;EI-Ebaishi, Karbhari & Naser, 2003;Guilding, Cravens & Tayles, 2000;Phadoongsitthi, 2003;Sulaiman, Ahmad & Alwi, 2004;Szendi & Elmore, 1993). Hence, it may be too early to conclude that traditional MAPs have completely lost their importance, and the adoption of contemporary MAPs may not guarantee the success of organizations.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this model has been tested by two studies in management accounting to determine the level of sophistication of MAPs (Adelegan, 2000;Abdel-Kader & Luther, 2006). The majority of the studies in terms of MAPs have been carried out in manufacturing sectors, (Adelegan, 2000;Sulaiman, et al, 2004;Wu & Drury, 2007;Davila, Wouters, 2006). However, the financial sector and services firms in general didn't have great attention from researchers and studies in terms of MAPs which was observed through reviewing the literature regarding management accounting studies.…”
Section: Research Significancementioning
confidence: 99%
“…In less-developed countries, Lin and Yu (2002) argued that the application of management accounting remains unsatisfactory. Sulaiman, et al (2004) indicated the lack of exploratory studies in Asian countries, in addition the need for studies which examine specific factors as to why Asian countries are not adopting newly developed management accounting tools and what the obstacles are to implementing such techniques. In Egypt, as a developing country, a study carried out by Ismail (2007) examined the performance measurement practices within private sector companies in Egypt.…”
Section: Materials Studiedmentioning
confidence: 99%
See 2 more Smart Citations